IMPLEMENTASI KEBIJAKAN PERMENKUMHAM NOMOR 27. TAHUN 2014 DALAM MENANGGULANGI PERMASALAHAN KEBERADAAN IMIGRAN (Studi Deskriptif di Kecamatan. Cisarua Kabupaten. Bogor) - Hariani, Fitri; Hernawan, Denny; Purnamasari, Irma (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2018)
This research is motivated by the immigrants who live in the District. Cisarua. Bogor Regency. The existence of immigrants which is a consequence of the development of human life must of course be limited and regulated existence. In that context there is Pemenkumham Number. 27 years. 2014 which can be used as a basis for policy to overcome the problems of immigrant existence.This research is quantitative by using descriptive method. Data collection techniques are conducted through interviews, questionnaires, literature studies, and documentation studies. Technique of data analysis to calculate questionnaire use weight mean score (WMS). The unit of analysis as the population studied is the subdistrict employee. Cisarua. District. Bogor, which amounted to 24 people. With this population, the sampling technique used is by means of saturated sampling or census.Â Keywords: Permenkumham, Immigrants, Immigration